2000
DOI: 10.1046/j.1440-1711.2000.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of lipopolysaccharide high‐dose paralysis in B‐cell responses: Implications for the one‐signal theory

Abstract: IntroductionLipolysaccharide (LPS), a component of the cell wall of gram-negative bacteria, is able to induce B cell activation resulting in proliferation and Ig production.1,2 Recently, Tolllike receptor 4 (Tlr4) has been implicated in the signalling pathway that leads to LPS-induced activation.3 However, how Tlr4 or other cellular components interact with LPS and induce cellular changes associated with differentiation is still poorly understood. Despite this lack of mechanistic information, a comprehensive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The varied effects of the different anti-Ig mAbs on cell division suggested that these reagents might differ qualitatively in their ability to signal via sIg. Different mitogenic properties of various anti-Ig reagents have been noted previously and attributed to qualitatively different signals delivered to the B cell as a result of different sIg cross-linking capacities (18,(51)(52)(53), their binding of different sIg epitopes (53,54), or coligation of Fc␥RIIb (55,56). This latter possibility was eliminated in this study by the inclusion of an antiFc␥RIIb mAb in selected experiments.…”
Section: Discussionmentioning
confidence: 63%
“…The varied effects of the different anti-Ig mAbs on cell division suggested that these reagents might differ qualitatively in their ability to signal via sIg. Different mitogenic properties of various anti-Ig reagents have been noted previously and attributed to qualitatively different signals delivered to the B cell as a result of different sIg cross-linking capacities (18,(51)(52)(53), their binding of different sIg epitopes (53,54), or coligation of Fc␥RIIb (55,56). This latter possibility was eliminated in this study by the inclusion of an antiFc␥RIIb mAb in selected experiments.…”
Section: Discussionmentioning
confidence: 63%
“…B cells were prepared from mouse spleen as described previously 10 , 19 . Briefly, a single cell suspension of murine spleen cells was prepared and consecutively depleted of red blood cells, with a lysis buffer (10 mmol/L potassium bicarbonate, 0.15 mol/L ammonium chloride, 0.1 mmol/L EDTA and 5% HI FCS, pH 7.3); adherent cells, by allowing cells to adhere to plastic Petri dishes; and T cells, using a cocktail of anti‐T cell antibodies (antimouse CD4, RL172 anti‐CD8, 31M and anti‐Thy1, 30H‐12 20 ) followed by rabbit complement (Cederlane Laboratories, Hornby, Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…When high concentrations of LPS are focused to the B cell surface by surface (s)Ig, however, the specific response is inhibited. Coutinho and Möller's one‐signal model assumed that this inhibition was due to high‐dose paralysis, 9 a phenomenon that our accompanying paper disputes 10 . As an alternative, we have proposed the hypothesis that the inhibition of ASC formation at high concentrations is due to B cells receiving a sIg‐mediated signal at the same time as the TI‐1 activation signal 11 .…”
Section: Introductionmentioning
confidence: 96%
“…Low-dose, low-affinity stimulation does not inhibit ASC differentiation but also has little effect on isotype switching. Thus, most Ab produced following these activation conditions will be low-affinity IgM Ab, as previously postulated (47,48). Although we remain unsure of the physiological relevance of these observations, it is possible that isotype-switched, high-affinity B cells are preferentially directed to a memory pool rather than to plasma cell differentiation.…”
Section: Discussionmentioning
confidence: 77%